An anti-inflammatory and low fermentable oligo, di, and monosaccharides and polyols diet improved patient reported outcomes in fibromyalgia: A randomized controlled trial - Silva, Ana Rita; Bernardo, Alexandra; de Mesquita, Maria Fernanda; Vaz-Patto, José; Moreira, Pedro; Silva, Maria Leonor; Padrão, Patrícia (Frontiers in Nutrition, 2022)
Background: Fibromyalgia (FM) has been associated with dysbiosis and low-grade inflammation. Studies have reported that diet influence clinical features in FM. Objective: To evaluate the effect of an anti-inflammatory and low fermentable oligo, di- and monosaccharides and polyols (FODMAP) diet in clinical outcomes of FM patients. Methods: This two arms Randomized Controlled Trial (NCT04007705) included 46 FM female patients. Intervention group (n=22) adopted an anti-inflammatory diet for 3 months, excluding gluten, dairy, added sugar and ultraprocessed foods, along with a low FODMAPs diet in the first month. Control group (n=24) followed general healthy eating recommendations. Both diets were applied by a certified dietitian. Before and after intervention, participants were assessed regarding pain, fatigue, gastrointestinal symptoms, quality-of-sleep and quality-of-life, through: Revised Fibromyalgia Impact Questionnaire (FIQR), Visual Analogue Pain Scale (VAS), Visual Analogue Scale from gastrointestinal symptoms (VAS GI), Brief Pain Inventory (BPI), Pittsburg Sleep Quality Index (PSQI), Fatigue Severity Survey (FSS) and The Short Form Health Survey (SF-36). A blood sample was collected and High-sensitive C-Reactive Protein and Erythrocyte Sedimentation Rate were quantified. Paired Samples T-Test/Wilcoxon and independent samples T-Test/Mann-Whitney were used to compare variables between groups. Results: After intervention, there was an improvement in intervention group scores of FIQR (p=0.001), VAS (p=0.002), BPI (p=0.011), FSS (p=0.042), VAS_GI (p=0.002), PSQI (p=0.048), and SF36 (p=0.045) compared to control group. Inflammatory biomarkers (hs-CRP, ESR) did not change in both groups. The intervention was beneficial in the intervention group, regardless of age, disease duration, body mass index variation and body fat changes between baseline and post-intervention. Conclusion: An anti-inflammatory and low-FODMAP diet improved clinical features in FM patients and may be useful as a complement to pharmacological therapy.